2019
DOI: 10.1002/sctm.19-0271
|View full text |Cite
|
Sign up to set email alerts
|

Autologous adipose-derived stem cells for the treatment of complex cryptoglandular perianal fistula: A randomized clinical trial with long-term follow-up

Abstract: The aim of this clinical trial (ID Number NCT01803347) was to determine the safety and efficacy of autologous adipose‐derived stem cells (ASCs) for treatment of cryptoglandular fistula. This research was conducted following an analysis of the mistakes of a same previous phase III clinical trial. We designed a multicenter, randomized, single‐blind clinical trial, recruiting 57 patients. Forty‐four patients were categorized as belonging to the intent‐to‐treat group. Of these, 23 patients received 100 million ASC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 33 publications
6
68
0
3
Order By: Relevance
“…Our study indicated that the closure rate of ADSC was not inferior to that of ERAF at week 12 (54.55% VS 53.85%, p = 1.000). And it was similar to some other studies [ 15 , 19 ]. As Cho et al [ 32 ] and Choi et al [ 17 ] reported, we also thought that some failure of the cases with ADSC in this study may be caused by poor control of infection.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study indicated that the closure rate of ADSC was not inferior to that of ERAF at week 12 (54.55% VS 53.85%, p = 1.000). And it was similar to some other studies [ 15 , 19 ]. As Cho et al [ 32 ] and Choi et al [ 17 ] reported, we also thought that some failure of the cases with ADSC in this study may be caused by poor control of infection.…”
Section: Discussionsupporting
confidence: 91%
“…We still believed that ADSC has an advantage in pain relief. On the other hand, there was no incontinence due to the injury of sphincter in the study as previously literatures reported (Table 1 ) [ 14 19 ]. The damage of anal function after the operation of ERAF may be related to the stretch injuries to the muscle and nerve fibers caused by significant retraction and manipulation of the anus [ 33 ].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The CSC niches allow the cell to remain dormant for a long time before initiating recurrent/distance metastasis [170] . Therefore, targeting whole tumor will not produce good results while targeting CSCs [171] . Furthermore, the cancer stem cells derived-exosomes are also crucial for tumor relapse, metastasis and maintenance.…”
Section: Various Molecular Approaches/signaling Pathways For Targetinmentioning
confidence: 99%